2013
DOI: 10.1177/0306624x13489864
|View full text |Cite
|
Sign up to set email alerts
|

Age of Crime Onset and Psychopathic Traits in Female Juvenile Delinquents

Abstract: The aim of this study was to analyze the role of psychopathic traits in the age of crime onset of female juvenile delinquents. Using a sample of 132 young females from the Juvenile Detention Centers of the Portuguese Ministry of Justice and from schools in the Lisbon region, a group of early crime onset (n = 44), a group of late crime onset (n = 44), and a nondelinquent school group (n = 44) were formed. Results showed that early crime onset participants score higher on psychopathy measures, self-reported deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…This means that even among sexual offenders characterized by considerable ACEs and deviant sexual behaviors, the enduring risk posed by their arrest history and initiation of that arrest history was more strongly associated with the most serious forms of criminal violence. The association between early age of arrest onset and serious criminal violence is consistent with prior studies (Pechorro, Gonçalves, Marôco, Nunes, and Jesus, 2014;Pechorro, Maroco, Gonçalves, Nunes, and Jesus, 2014;Torok et al, 2012;Trojan and Salfati, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…This means that even among sexual offenders characterized by considerable ACEs and deviant sexual behaviors, the enduring risk posed by their arrest history and initiation of that arrest history was more strongly associated with the most serious forms of criminal violence. The association between early age of arrest onset and serious criminal violence is consistent with prior studies (Pechorro, Gonçalves, Marôco, Nunes, and Jesus, 2014;Pechorro, Maroco, Gonçalves, Nunes, and Jesus, 2014;Torok et al, 2012;Trojan and Salfati, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…The correlations of the PCL:YV total score, the three-factor model and its dimensions with criminal variables revealed mostly the existence of moderate-low negative associations with age of crime onset, and the existence of moderate-low positive associations with the frequency of crimes, the number of victims, and the use of physical violence, with the exceptions of the Interpersonal and the Affective dimensions which revealed mostly non-significant correlations. Negative associations between psychopathy scores and the age of crime onset have been consistently reported in the literature (e.g., Brandt cited in Forth et al, 2003;Bauer cited in Forth et al, 2003;Pechorro, Gonçalves, Marôco, Nunes, & Jesus, 2013), although the one we obtained was somewhat lower but still statistically significant. Positive associations between PCL:YV scores similar to the ones we obtained have been consistently reported in the literature (e.g., Forth et al, 2003;Marshall et al, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…Pechorro et al . found that younger age of crime onset was closely associated with psychopathic-traits 33 , but Males and Brown argued that the association of violence with young age was probably mediated by poverty amongst youth 32 . The close relationship between socioeconomic background and violence has been frequently reported across different areas and ethnic races 19 .…”
Section: Discussionmentioning
confidence: 99%